2024
DOI: 10.1021/acs.nanolett.4c01166
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency and Stable Colloidal One-Dimensional Core/Shell Nanorod Light-Emitting Diodes

Yicheng Zeng,
Shaolin Ma,
Fan Cao
et al.

Abstract: Anisotropic nanocrystals such as nanorods (NRs) display unique linearly polarized emission, which is expected to break the external quantum efficiency (EQE) limit of quantum dot-based light-emitting diodes (LEDs). However, the progress in achieving a higher EQE using NRs encounters several challenges, primarily involving a low photoluminescence quantum yield (PLQY) of NRs and imbalanced charge injection in NR-LEDs. In this work, we investigated NR-LEDs based on CdSe/CdZnS/ ZnS rod-in-rod NRs with a high PLQY a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…These results correspond well with previously published reports [ 29 , 31 , 32 ]. The anisotropy value is increased from 0.203 of CdSeTe/CdS NRs to 0.221 of CdSeTe/CdZnS/ZnS NRs, which is due to the more uniform morphology of CdSeTe/CdZnS/ZnS NRs and the radial distribution of Zn in the CdZnS shell [ 33 ]. Note that the amount of Zn-OA must be precisely controlled, since high Zn content in the CdZnS shell will accumulate an excess strain to the CdSeTe core and increase the interface defect density, resulting in a lower PL intensity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results correspond well with previously published reports [ 29 , 31 , 32 ]. The anisotropy value is increased from 0.203 of CdSeTe/CdS NRs to 0.221 of CdSeTe/CdZnS/ZnS NRs, which is due to the more uniform morphology of CdSeTe/CdZnS/ZnS NRs and the radial distribution of Zn in the CdZnS shell [ 33 ]. Note that the amount of Zn-OA must be precisely controlled, since high Zn content in the CdZnS shell will accumulate an excess strain to the CdSeTe core and increase the interface defect density, resulting in a lower PL intensity.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, such core–shell structures have been increasingly explored in NRs [ 29 , 30 ]. Recently, Zeng et al reported CdSe/CdZnS/ZnS NRs and CdSe/CdZnS/CdZnS/ZnS NRs with carefully designed multilayer shell structures, achieving the highest EQE of red NR-LEDs to date [ 31 , 32 , 33 ]. However, reports on the tunability of the emission wavelength of NRs are not as comprehensive as those on QDs.…”
Section: Introductionmentioning
confidence: 99%